O CASO CLIMADAPT.LOCAL: CAPACITAÇÃO E AÇÃO CLIMÁTICA EM PORTUGAL - Guerra, João Francisco (2021)
In an era where climate change gained relevance and caused the highest levels of social awareness, the main objective of ClimAdaPT.Local project valued the integration of the climate dimension in municipal planning processes. Based on a questionnaire survey applied in three consecutive rounds throughout the project, this article focuses on the responses of a group of municipal officers who, together with the ClimAdaPT.Local team, developed Municipal Strategies for Adaptation to Climate Change. With the focus on the respondents' evolution concerning acquisition of knowledge, mobilization and awareness, and capacity building throughout the project, the main conclusions will be presented here.